SEASONAL VARIATIONS IN HAEMATOLOGICAL INDICES IN THE GREY BREASTED GUINEA FOWL (Numida Meleagris Galeata Pallas) - ONYEYILI, P. A.; EGWU, G. O.; JIBIKE, G. I.; PEPPLE, D. L.; OHAEGBULAM, J. O. (Nigerian Journal of Animal Production, 2021)
The influence of seasons on the haematological indices were studied in the grey breasted guinea fowl (Numida meleagris galeata pallas) in the arid zone of Borno State. Blood samples for haematological analysis were collected from the wing vein of the birds. The RBC counts and PCV values were significantly (P<0.05) increased during the hot weather period compared to the values obtained in the cold period. This increase may be due to decreased plasma volume resulting from increase in body water loss at high ambient temperatures